Examining the teachers’ pedagogical knowledge and learning facilities towards teaching quality - Muhd Zulhilmi Haron; Mohd Muslim Md Zalli; Mohamad Khairi Othman; Mohd Isha Awang (International Journal of Evaluation and Research in Education (IJERE), 2021)
The purpose of this study was to examine the relationship between teachers’ pedagogical knowledge, learning facilities and the teaching quality of teachers in the Ulul Albab Tahfiz Model (TMUA) schools in Malaysia. The data were collected using a set of questionnaires which probed on the respondents’ demographic information as well as on their pedagogical knowledge, learning facilities and teaching quality. The respondents comprised of 144 teachers from three schools involved in TMUA program. The data obtained were processed and analysed through the Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS 3.0 software. The results show that there is a significant relationship between teachers’ pedagogical knowledge, educational facilities and the quality of teaching. The implication of this study is that teachers are aware of the importance of pedagogical knowledge in improving teaching quality when implementing the TMUA program.